2004
DOI: 10.7589/0090-3558-40.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Viral Infections in Free-Ranging Namibian Cheetahs (Acinonyx Jubatus)

Abstract: Cheetahs (Acinonyx jubatus) in captivity have unusually high morbidity and mortality from infectious diseases, a trait that could be an outcome of population homogeneity or the immunomodulating effects of chronic stress. Free-ranging Namibian cheetahs share ancestry with captive cheetahs, but their susceptibility to infectious diseases has not been investigated. The largest remaining population of free-ranging cheetahs resides on Namibian farmlands, where they share habitat with domestic dogs and cats known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 20 publications
2
68
1
1
Order By: Relevance
“…1 Transmission of viruses (FPV, Felid herpesvirus 1, FCoV, and FCV) between cheetahs and domestic cats has previously been described. 11,17 Astroviruses are considered to be species-specific viruses, but interspecies transmission and/or recombination between either related or unrelated species has been hypothesized, involving cows and red deer, human beings and marine mammals, and human beings and/or ruminants/minks. 10,16,22 Interestingly, in the capsid gene (ORF2), FAstVs appear to resemble human AstVs more closely than other mammalian viruses, thus suggesting a relatively recent intersection in their evolution.…”
mentioning
confidence: 99%
“…1 Transmission of viruses (FPV, Felid herpesvirus 1, FCoV, and FCV) between cheetahs and domestic cats has previously been described. 11,17 Astroviruses are considered to be species-specific viruses, but interspecies transmission and/or recombination between either related or unrelated species has been hypothesized, involving cows and red deer, human beings and marine mammals, and human beings and/or ruminants/minks. 10,16,22 Interestingly, in the capsid gene (ORF2), FAstVs appear to resemble human AstVs more closely than other mammalian viruses, thus suggesting a relatively recent intersection in their evolution.…”
mentioning
confidence: 99%
“…The following methods were used: virus neutralization test (VNT) to detect CDV, FCV, and FHV1 antibodies; both Western blot and an enzyme-linked immunosorbent assay (ELISA) to detect FIV antibodies; ELISA to detect FeLV antigen; and hemagglutination inhibition/ 2-mercaptoethanol (HAI/2-ME) to detect FPV IgG antibodies (Harrison et al, 2004;Munson et al, 2004). Feline coronovirus (FCoV or FIPV) antibodies were determined by indirect immunofluorescence (IFA) at the Washington Animal Disease Diagnostic Laboratory, Pullman, Washington, USA (Harrison et al, 2004;Munson et al, 2004).…”
mentioning
confidence: 99%
“…Furthermore, several studies have reported the absence of seropositivity to FIV among non-domestic felids around the world (OLMSTED et al, 1992;SPENCER et al, 1992;BROWN et al, 1993;ROELKE et al, 1993, PAUL-MURPHY et al, 1994OSOFSKY et al, 1996;MUNSON et al, 2004;MILLÁN;RODRÍGUEZ, 2009;THALWITZER et al, 2010). Among 18 free-ranging Knowledge of the occurrence of these agents in captive non-domestic felids may contribute to future ecological investigations regarding the epidemiology of these pathogens among free-ranging non-domestic felids and domestic cats in Brazil.…”
Section: Discussionmentioning
confidence: 99%